Scanning Tunneling Microscopy and Scanning Electron Microscopy Observations of the Early Stage of Silver Deposition on Graphite Single Crystal Electrodes - Vázquez, L. (1992)
The early stages of Ag overpotential deposition on highly oriented pyrolytic graphite (HOPG) from Ag+-ion-containing acid solutions have been studied by ex situ scanning tunneling microscopy and scanning electron microscopy imaging complemented with electrochemical, energy dispersive X-ray analysis, and Auger electron spectroscopy data. Nucleation and 3D Ag growth initiate at surface defects. Unstructured 3D Ag nuclei decorating HOPG steps and flat geometric Ag islands are formed around the steps. The island structure is compatible with a local layer-by-layer growth. The entire morphology of the Ag deposit is consistent with a growth mechanism involving Ag atom diffusion from 3D nuclei at step edges toward Ag flat domains. Images with atomic resolution reveal large uncovered HOPG areas and Ag submonolayer domains with the nearest-neighbor distance d = 0.33 ± 0.02 nm, whereas flat Ag islands exhibit d = 0.29 ± 0.02 nm as expected for the nearest-neighbor distance in the Ag lattice. A model for these structures is discussed.